A method for the generation of ectromelia virus (ECTV) recombinants: in vivo analysis of ECTV vCD30 deletion mutants. - Ali Alejo; Margarida Saraiva; Maria Begoña Ruiz-Argüello; Abel Viejo-Borbolla; Mar Fernández de Marco; Francisco Javier Salguero; Antonio Alcami (PLoS ONE)
Background Ectromelia virus (ECTV) is the causative agent of mousepox, a lethal disease of mice with similarities to human smallpox. Mousepox progression involves replication at the initial site of infection, usually the skin, followed by a rapid spread to the secondary replicative organs, spleen and liver, and finally a dissemination to the skin, where the typical rash associated with this and other orthopoxviral induced diseases appears. Case fatality rate is genetically determined and reaches up to 100% in susceptible mice strains. Like other poxviruses, ECTV encodes a number of proteins with immunomodulatory potential, whose role in mousepox progression remains largely undescribed. Amongst these is a secreted homologue of the cellular tumour necrosis factor receptor superfamily member CD30 which has been proposed to modulate a Th1 immune response in vivo. Methodology/principal findings To evaluate the contribution of viral CD30 (vCD30) to virus pathogenesis in the infected host, we have adapted a novel transient dominant method for the selection of recombinant ECTVs. Using this method, we have generated an ECTV vCD30 deletion mutant, its corresponding revertant control virus as well as a virus encoding the extracellular domain of murine CD30. These viruses contain no exogenous marker DNA sequences in their genomes, as opposed to other ECTVs reported up to date. Conclusions/significance We show that the vCD30 is expressed as a secreted disulfide linked trimer and that the absence of vCD30 does not impair mousepox induced fatality in vivo. Replacement of vCD30 by a secreted version of mouse CD30 caused limited attenuation of ECTV. The recombinant viruses generated may be of use in the study of the role of the cellular CD30-CD30L interaction in the development of the immune response. The method developed might be useful for the construction of ECTV mutants for the study of additional genes.